Regulation of sleep disorders in patients with traumatic brain injury by intestinal flora based on the background of brain-gut axis - Zhanfeng, Niu; Liang, Wu; Jing, Kang; Jinbo, Bai; Yanjun, Chen; Hechun, Xia (Frontiers in Neuroscience, 2022)
Objective We look into whether there are changes of intestinal flora of the patients with sleep disorder after traumatic brain injury, and the changes may allow us to get more understanding of the role of intestinal flora in sleep disorders in patients after traumatic brain injury, which may give us a clue to cure the sleep disorder after traumatic brain injury(TBI). Method We analyzed the intestinal microbial colony structure in the feces of the 28 patients in the normal sleep group and the sleep disorder group by 16SrDNAsequencing technology. The bioinformatics method was used to analyze the change of the intestinal flora in v3-v4 region of patients with biorhythm disorder, and to observe the difference between the two groups. Results Group grouping comparison and analysis of evolutionary cladistic map showed the intestinal flora of patients with normal sleep after TBI was mainly Bacilli and Lactobacillales, while that of patients with sleep disorder was mainly Lachnospiraceae and Bacteroidales. Histogram of Group value distribution by grouping comparison and analysis showed Bacilli, Lactobacillales, Streptococcus and Veillonella were dominant in normal sleep group, and Lachnospiraceae, Bacteroidales, Bacteroidia and Bacteroidetes were dominant in sleep disorder group. Relative abundance map of species with significant differences by Group grouping comparison showed the main manifestations of intestinal flora are Firmicutes, Bacilli, Lactobacillales, Streptococcaceae and Bacteroidetes. The normal sleep group was dominated by Bacilli, Lactobacillales, Streptococcus and Veillonella, while in the sleep disorder group, Lachnospiraceae, Bacteroidales, Bacteroidia and Bacteroidetes were the main species. It was found that there were also significant differences in intestinal flora abundance between the two groups after TBI. After statistics processing, it was indicated compared with the normal sleep group, Lactobacillus, Streptococcus, Oribacterium and Rothia, Actinomyces, Streptophyta, TM7-3 bacteria and Serratia showed a significant reduction in the sleep disorder group (P<0.05). However, the Odoribacter, Lachnospiraceae and Bilophila increased significantly (P<0.05). Conclusion The sleep disorders of patients after TBI can be closely related to the disturbance of intestinal flora, and its internal mechanism needs further study. Intestinal flora has the potential to be a new therapeutic target.